The Evolutionary Stability of Optimism, Pessimism, and Complete Ignorance - Burkhard Schipper (University of California, Department of Economics, 2019)
We seek an evolutionary explanation for why in some situations humans maintain either optimistic or pessimistic attitudes towards uncertainty and are ignorant to relevant aspects of their environment. Players in strategic games face Knightian uncertainty about opponents' actions and maximize individually their Choquet expected utility with respect to neo-additive capacities (Chateauneuf, Eichberger, and Grant, 2007) allowing for both an optimistic or pessimistic attitude towards uncertainty as well as ignorance to strategic dependencies. An optimist (resp. pessimist) overweights good (resp. bad) outcomes. A complete ignorant never reacts to opponents' changes of actions. We focus on sub- and supermodular aggregative games and provide monotone comparative statics w.r.t. optimism/pessimism. With qualifications we show that in finite populations optimistic (resp. pessimistic) complete ignorance is evolutionary stable and yields a strategic advantage in submodular (resp. supermodular) games with aggregate externalities. Moreover, this evolutionary stable preference leads to Walrasian behavior in these classes of games.
Keywords: C72; C73; D01; D43; D81; L13; 330; ambiguity; Knightian uncertainty; Choquet expected utility; neo-additive capacity; Hurwicz criterion; Maximin; Minimax; supermodularity; aggregative games; monotone comparative statics; playing the field; evolution of preferences